Parameterized computational complexity of finding small-diameter subgraphs - Schäfer, Alexander; Komusiewicz, Christian; Moser, Hannes; Niedermeier, Rolf (Optimization letters, 2012)
Finding subgraphs of small diameter in undirected graphs has been seemingly unexplored from a parameterized complexity perspective. We perform the first parameterized complexity study on the corresponding NP-hard s - Club problem. We consider two parameters: the solution size and its dual.